Asset Pricing in the Dark: The Cross-Section of OTC Stocks - Ang, Andrew; Shtauber, Assaf A.; Tetlock, Paul C. (Review of Financial Studies, 2013)
[Over-the-counter (OTC) stocks are far less liquid, disclose less information, and exhibit lower institutional holdings than do listed stocks. We exploit these different market conditions to test theories of cross-sectional return premiums. Compared with premiums in listed markets, the OTC illiquidity premium is several times higher, the size, value, and volatility premiums are similar, and the momentum premium is three times lower. The OTC illiquidity, size, value, and volatility premiums are largest among stocks held predominantly by retail investors and those not disclosing financial information. Theories of differences in investors' opinions and limits on short sales help explain these return premiums.]